H.J. Heinz and Global Gardens: Creating Quality, Leveraging Localities - McKenna, Megan; Rochea , Michael; Le Heron, Richard (The International Journal of Sociology of Agriculture and Food, 2021)
This article discusses the expansion and production strategies within New Zealand of transnational food giant H.J. Heinz. Operating through the established brands of the ‘local’ food processor J. Wattie, which it purchased in the early 1990s, Heinz has continued its cautious but steady transnational growth policy into new global markets. Taking advantage of New Zealand’s deregulated economy since the late 1980s, Heinz is leveraging competitive labour rates and a ‘clean green’ image in New Zealand to consolidate its position as the key supplier of canned and frozen foods to selected large Asian markets. In essence, the take over of Watties, New Zealand’s leading food processor, enables Heinz to draw on existing supply and marketing networks to position New Zealand as an ‘oasis market garden’ for Asia. The purposes of this article are twofold. First to explore the growing significance of Heinz challenging frozen food myths in fostering the development of organic food processing as part of its expansionist programme, especially in the context of the recent Asian ‘economic crisis’. And second, to evaluate the shifting relationships Heinz has developed with contract growers in the context of global economic competitiveness and neo-liberal thinking.